Recovery of Co from aqueous solutions using nanodiamonds as solid adsorbents. Issue 1 (10th October 2016) - Reina, Giacomo; Peruzzi, Carlotta; Orlanducci, Silvia; Terranova, Maria Letizia
Abstract : A study has been carried out to test detonation nanodiamond (DND) as solid adsorbent for the recovery of Co ions from wastewater. With the aim to enhance the surface affinity for Co ions, after preliminary purification and oxidation steps, the DNDs were functionalized with three different diamine chelant molecules. The as prepared materials were characterized via FT‐IR and TGA. Finally, the Co adsorption capacity of DND was obtained by quantifying, by means of UV‐Vis spectroscopy, the residual concentration of Co ions in the solutions. Playing with the surface chemistry of DND it was possible to strongly enhance the DND uptake of cobalt ions, up to a value of about 60%. The proposed process offers flexibility in design and operation and the proper functionalized DNDs demonstrated to be effective solid adsorbent systems for metal recycling. Top left: cartoon of the amidation reaction of the DND surface; top right: thermogravimetric analysis of the pristine and functionalized DNDs; bottom left: scheme of the Co absorption experiments made with the various DNDs in the Co solution, bottom right: UV‐Vis spectra of the various Co standard solutions.